Photopic flicker optoretinography captures the light-driven length modulation of photoreceptors during phototransduction - Sławomir Tomczewski; Andrea Curatolo; Andrzej Foik; Piotr Węgrzyn; Bartłomiej Bałamut; Maciej Wielgo; Wiktor Kulesza; Anna Galińska; Katarzyna Kordecka; Sahil Gulati; Humberto Fernandes; Krzysztof Palczewski; et al. (Proceedings of the National Academy of Sciences, 2025)
In this study, we used an inhibitor of phosphodiesterase 6 (PDE6) to examine the impact of changes in the conformation of the PDE6 protein on the light-induced process responsible for altering the length of the outer segments of photoreceptor cells in both human and rodent eyes. We employed a imaging method called spatiotemporal optical coherence tomography, which ensures high contrast and phase stability within the strongly scattering photoreceptor– Retinal Pigment Epithelium complex. Using this approach, we recorded nanometer-scale changes in human cones and rods in response to photopic flicker stimulation and observed length changes in rodent rods under scotopic conditions following a single pulse of light, in the absence or presence of sildenafil, which inhibits the catalytic activity of PDE6. Our findings are consistent with the interpretation that during phototransduction conformational changes in PDE6 structure, which occur on an angstrom scale, are amplified to the nanometer scale due to the unique structure of the photoreceptor outer segments and sequential stimulation. This finding opens up possibilities for the informed use of photopic flicker optoretinography measurements as a diagnostic tool, as the observed nanometer-scale changes in rod and cone dimensions as a function of light stimulus can now be directly linked to molecular events involved in the phototransduction pathway.